2016
DOI: 10.11005/jbm.2016.23.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Osteocalcin with Insulin Resistance and Coronary Atherosclerosis

Abstract: BackgroundTo determine the associations between serum osteocalcin level and insulin resistance, coronary atherosclerosis by using dual-source coronary computed tomography angiography.MethodsA total of 98 subjects (24 men and 74 women) were selected for this retrospective cross-sectional study who voluntarily visited a health examination center for routine health check-up including the blood test for serum osteocalcin level and coronary computed tomography angiography. Multiple regression analysis was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Week a b c Vitamin K is necessary to carboxylate osteocalcin and deficiency results in increased risk of fracture. 2,3,7,25 An analysis of blood samples from 896 persons suggested that most people do not receive enough vitamin K from their diet (32). 26 The best vitamin K to improve vitamin K status is long-chained MKs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Week a b c Vitamin K is necessary to carboxylate osteocalcin and deficiency results in increased risk of fracture. 2,3,7,25 An analysis of blood samples from 896 persons suggested that most people do not receive enough vitamin K from their diet (32). 26 The best vitamin K to improve vitamin K status is long-chained MKs.…”
Section: Discussionmentioning
confidence: 99%
“…Beside its role in bone tissue osteocalcin is a hormone affecting diverse functions such as metabolism, adaptation to exercise and brain function. 2,3,5,7 In mice, these effects have been attributed to undercarboxylated osteocalcin, but in several human studies osteocalcin or only carboxylated osteocalcin rather than the undercarboxylated have shown effects. [30][31][32][33] The present results indicate intake of Jarlsberg ® cheese to cause both carboxylated and under carboxylated osteocalcin to increase.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the association of cytokines (e.g., osteocalcin) with bone metabolism and growth is known and is to be expected [28]. Here, we added data on sclerostin and osteoprotegerin as independent predictors of height SDS.…”
Section: Discussionmentioning
confidence: 99%
“…Serum osteocalcin levels in women with T2DM are lower compared with nondiabetic women [17,18]. Moreover, there is an inverse association between serum osteocalcin levels and both fasting glucose levels and insulin resistance [19]. Incretins have also been implicated in the pathogenesis of increased fracture risk in patients with T2DM.…”
Section: T2dm and Fracturesmentioning
confidence: 99%